Trimetallic PdCuAu Nanoparticles for Temperature Sensing and Fluorescence Detection of H2O2 and Glucose - Nie, Furong; Ga, Lu; Ai, Jun; Wang, Yong (Frontiers in Chemistry, 2020)
The design of palladium-based nanostructures has good prospects in various applications. This paper reports a simple one-step synthesis method of PdCuAu nanoparticles (PdCuAu NPs) prepared directly in aqueous solution. PdCuAu NPs have attracted much attention owing to their unique synergistic electronic effect, optical and catalytic performance. As temperature sensor, PdCuAu NPs are sensitive to the fluorescence intensity change in the temperature range of 4-95 °C, which is due to its unique optical properties. The prepared PdCuAu NPs have excellent catalytic performance for peroxidase-like enzymes. It can catalyze TMB rapidly in the presence of hydrogen peroxide and oxidize it to visible blue product (oxTMB). Based on its unique peroxidase-like properties, this study used PdCuAu NPs colorimetric platform detection of hydrogen peroxide and glucose. The linear ranges of hydrogen peroxide and glucose were 0.1-300 µM and 0.5-500 µM, respectively, and the detection limits (LOD) were 5 nM and 25 nM, respectively. This simple and rapid method provides a good prospect for the detection of H2O2 and glucose in practical applications.